2021
DOI: 10.1002/anie.202103872
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Noncanonical Features of the Nonlinear Nonribosomal Peptide Synthetase Assembly Line for WS9326A Biosynthesis

Abstract: Systematic inactivation of nonribosomal peptide synthetase (NRPS) domains and translocation of the thioesterase (TE) domain revealed several unprecedented nonlinear NRPS assembly processes during the biosynthesis of the cyclodepsipeptide WS9326A in Streptomyces sp.SNM55. First, two sets of type II TE (TEII)-like enzymes mediate the shuttling of activated amino acids between two sets of standalone adenylation (A)-thiolation (T) didomain modules and an "A-less" condensation (C)-T module with distinctive specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Another NRPS activates and transfers l - allo -threonine to the module with the missing A domain ( 32 ). RthD, a type II thioesterase-like (TEII) enzyme, is believed to assist in the shuttling of the activated aThr between the stand-alone A-T didomain module RthB and the A-less C-T module of RthA, as described previously for WS9326A biosynthesis ( 33 ). A serine residue was predicted in module 3, but (2,4)-di-amino butyric acid was observed.…”
Section: Resultsmentioning
confidence: 84%
“…Another NRPS activates and transfers l - allo -threonine to the module with the missing A domain ( 32 ). RthD, a type II thioesterase-like (TEII) enzyme, is believed to assist in the shuttling of the activated aThr between the stand-alone A-T didomain module RthB and the A-less C-T module of RthA, as described previously for WS9326A biosynthesis ( 33 ). A serine residue was predicted in module 3, but (2,4)-di-amino butyric acid was observed.…”
Section: Resultsmentioning
confidence: 84%
“…Interpretation of the structures of the accumulated products in these variants provided conclusions that two TE II domains, WS5 and WS20, are highly likely to act as shuttling enzymes to translocate the activated L- allo -Thr and L-Asn from WS22 and WS23, respectively, to the downstream iterative module 7, which adds these two amino acids to the growing peptide chain. MST analysis revealed considerably high binding affinities between WS5- apo -WS23, WS20- apo -WS22 and WS20- apo -WS23 while relatively low binding affinities between WS5- apo -WS22 39 . Crystallographic studies of WS5 and structural modelling suggested possible PPIs between WS5 and the T domains of WS22/23.…”
Section: Discussionmentioning
confidence: 96%
“…For example, WS9326A, a specialised cyclodepsipeptide isolated from various Streptomyces , exhibits several interesting chemical features, such as an ( E )-2,3-dehydrotyrosine and a ( Z )-pentenylcinnamoyl moiety. 36 38 Analysis of the corresponding ws BGC 39 indicated the presence of two standalone upstream modules (WS22 and WS23) consisting of an A-T didomain, two TE II domains (WS5 and WS20, respectively), and the adjacent downstream module 7 with an arrangement of C-T-C-A-T, similar to LgnD. The two A domains in WS22 and WS23 were predicted to activate L- allo -Thr and L-Asn, respectively, key chemical moieties of WS9326A 39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations